The challenge of peptide nucleic acid synthesis. (3rd April 2023) - Nandhini, K. P.; Shaer, Danah Al; Albericio, Fernando; de la Torre, Beatriz G.
Abstract : The main strategies for the synthesis of Peptide Nucleic Acids (PNAs): key molecules as DNA/RNA mimics that can hybridize complementary chains of nucleic acids with high affinity and specificity. Abstract : Peptide nucleic acids (PNAs) are an important class of DNA/RNA mimics that can hybridize complementary chains of nucleic acids with high affinity and specificity. Because of this property and their metabolic stability, PNAs have broad potential applications in different fields. Consisting of a neutral polyamide backbone, PNAs are prepared following the method used for peptide synthesis. In this regard, they are prepared by the sequential coupling of the protected monomers on a solid support using a similar approach to solid-phase peptide synthesis (SPPS). However, PNA synthesis is a little more challenging due to issues of the difficulty on the preparation of monomers and their solubility. Furthermore, the PNA elongation is jeopardized by intra/inter chain aggregation and side reactions. These hurdles can be overcome using different protecting group strategies on the PNA monomer, which also dictate the approach followed to prepare the oligomers. Herein, the main synthetic strategies driven by the protecting group scheme are discussed. However, there is still ample scope for further enhancement of the overall process.